The Association of Liposomal Bupivacaine on Opioid Consumption in the Pediatric Alveolar Cleft Population. Issue 4 (June 2020) - Crowley, Jiwon Sarah; McLean, Paige; Gabriel, Rodney A.; Cronin, Brendan; Hsieh, Sun; Englar, Kevin; Said, Engy; Lance, Samuel; Gosman, Amanda
Abstract : Abstract: Surgical infiltration of liposomal bupivacaine in the adult population has been shown to decrease perioperative use of opioids, but there have been few studies conducted in the pediatric surgical population. The authors' objective was to assess the effect of liposomal bupivacaine on opioid reduction in the pediatric alveolar cleft population. The authors hypothesized that the use of surgical site infiltration with liposomal bupivacaine would be associated with decreased post-operative opioid requirements following alveolar bone grafting. The authors performed a retrospective cohort study at a tertiary craniofacial center. Forty-four pediatric patients undergoing alveolar bone grafting from November 2016 to December 2018 by the 2 craniofacial surgeons at Rady Children's Hospital were included in the study. Surgical site infiltration with liposomal bupivacaine was performed and the amount of oral morphine equivalents administered within the first 24 hours was measured. Patients in the liposomal bupivacaine cohort required 12.0 mg OME less than those patients who received standard bupivacaine or 1% lidocaine. When controlling for age, sex, weight, laterality, and harvest technique, multivariable linear regression analysis demonstrated a difference of 15.7 mg OME in favor of the LB cohort ( P  = 0.0006). The authors' study revealed that intraoperative surgical site infiltration of liposomal bupivacaine was associated with decreased post-operative opioid requirements following alveolar bone grafting. It should be considered as an effective part of multimodal pain therapy in the pediatric surgical population. Abstract : Supplemental Digital Content is available in the text